Molecular dynamics study of phonon transport in graphyne nanotubes. (October 2017) - Ramazani, A.; Reihani, A.; Soleimani, A.; Larson, R.; Sundararaghavan, V.
Abstract: We determine the thermal conductivities of α, β, and γ graphyne nanotubes (GNTs) as well as of carbon nanotubes (CNTs) using molecular dynamics simulations and the Green-Kubo relationship over the temperature range 50–400 K. We find that GNTs demonstrate considerably lower thermal conductivity than CNTs with the same diameter and length. Among α, β, and γ-GNTs, γ-GNT has the highest thermal conductivity at all temperatures. By comparing the phonon transport properties of GNTs with CNTs, we find that as the fraction of acetylene bonds in the atomic network increases, the population of high-energy optical phonons increases. This enhances phonon-phonon scattering, and reduces the mean free path, adversely affecting the thermal conductivity of GNTs relative to CNTs. Also reducing the thermal conductivity of GNTs relative to CNTs is the considerably lower acoustic phonon group velocities for the former as well as the lower volumetric heat capacity of GNTs. Optical phonons in α-GNT are high in energy (0.26 eV) with a high population number, making them more energetic than the electronic direct band gap and significantly more energetic than the thermal energy at room temperature. Therefore, we suggest α-GNT as a potential candidate for phonovoltaic energy conversion applications. Graphical abstract: